The diaoyu/senkaku dispute in the context of China- U.S.-Japan trilateral dynamics - Zhang, Yun (2014)
Why has China been more assertive and resolute towards Japan in dealing the Diayu/Senkaku dispute since 2010? What logic has guided China’s new strategy and policy? How should we assess the effectiveness of China’s approach? This paper seeks to demonstrate that a trilateral perspective on U.S., Chinese, and Japanese relations is vital for answering these questions. In the current conjuncture – one that is shaped by global economic turbulence and a rebalancing of U.S. power towards Asia – China perceives the Diaoyu/Senkaku dispute as a key moment for establishing a new, great power relationship with the United States, one that works behind a façade of Sino-Japanese confrontation. The dynamic adjustments in U.S. –China relations over the past several years is the primary variable in China’s approach to dealing with this dispute, which seems to have replaced Taiwan as the test of U.S.-China strategic intents and military capabilities in the western Pacific. China does not deny or neglect the U.S-Japanese relationship, but strongly opposes any form of anti-Chinese alliance on this matter. Several factors have discouraged a proactive Chinese policy toward Japan since 2010. These include previous failures in Sino-Japanese diplomacy divisions within Japan on these issues, and the Chinese perception of a dramatic right-wing turn in Japan. For these reasons, China seeks only a passive engagement with Japan, focusing instead on Sino-U.S. relations as the core dynamic of this dispute. In the immediate term, China’s new assertiveness on this issue have produced several consequences, including a fortification of the U.S.-Japanese alliance, movement towards autonomous military capacity building in Japan, and spill over concern for other ASEAN countries, However, China seems to believe that clearer signals of its intentions would help reduce miscalculations and accelerate the long-term repositioning of Sino-U.S. relations. On strategic grounds, it might be politically wise and cost-effective for China to concentrate its resources on repositioning U.S.-Sino relations. But, on tactical grounds, this less-balanced approach might risk damaging China’s soft power. Without sophisticated public diplomacy, China’s statements and actions towards Japan might alienate the Japanese public and deleteriously affect China’s image. In this sense, it would be tactically astute for China to be sensitive to public opinion in Japan and to invest more resource and effort in public diplomacy in Asia.